DINAMIKA KELOMPOK TANI DI DESA NUNKURUS KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Erni Dida; Made Tusan Surayasa; Serman Nikolaus (Buletin Ilmiah Impas, 2020)
ABSTRACT This research was conducted in Nunkurus Village, East Kupang District, Kupang Regency. Data collection was carried out in April-June 2019. The purpose of this study was to: determine the level of dynamics of farmer groups in Nunkurus Village, East Kupang Subdistrict, Kupang Regency, and to analyze the relationship between socio-economic factors and the level of dynamism of farmer groups in Nunkurus Village, East Kupang Subdistrict, Kupang Regency in trying to farm. The location of the study was determined intentionally (purposive sampling), while the respondents were determined by means of professional random sampling of members of farmer groups, and intentionally towards the chairmen and secretaries of each farmer group. The number of respondents was 48 people. The type of data collected is primary data and secondary data. Data collected was analyzed using a Likert Scale, and Sperman Rank nonparametric statistical tests. The results showed that: (1) the dynamics of farmer groups in Nunkurus Village, East Kupang District, Kupang Regency was classified as "quite dynamic" (65%). The atmosphere of the group contributes the most, namely 70% while the element of developing and fostering the group contributes only 60%, and (2) the socioeconomic factor of the level of education has a significant relationship with the dynamics of the farmer group in Nunkurus Village. While socio-economic factors of age, experience of farming, land area and number of family dependents have insignificant relationship with the dynamics of farmer groups in Nunkurus Village, East Kupang District, Kupang Regency.